The Affecting Electricity Consumption in Indonesia - Fika Akhrani, Elsa; Marselina, Marselina (Lafadz Jaya Publisher, 2023)
This research aims to analyze the factors that influence electricity consumption in Indonesia. The data used in this research is panel data for 2020-2022 in 32 provinces in Indonesia. The analysis technique used is Multiple Regression Analysis with Random Effect Model (REM). The dependent variable used is electricity consumption and the independent variables include electricity prices, income and number of customers. The research results show that the price of electricity has a negative and significant effect on electricity consumption. Meanwhile, income and number of customers have a positive and significant effect on electricity consumption. Simultaneously, electricity prices, income and number of customers have a significant effect on electricity consumption.